The Effect of Maturity Quality of Kepok Banana on the Sweetness Level of Banana Sale - Muhammad Haikal Hafiz; Devi Tanggasari (Universitas Muhammadiyah Mataram, 2023)
One of the preparations that can be made with the basic ingredients of kepok bananas is banana sale. Processed banana sale in this study used three levels of banana ripeness, namely greenish yellow, shiny yellow, and brownish yellow with black spots. The purpose of this study was to determine the reduction in mass in the manufacture of sale bananas, to determine the level of sweetness of sale bananas from three different maturity levels, to determine the drying time of bananas from different maturity levels with various water content, and to determine the preference level of the three maturity levels. banana sale. The method used is the RAK method (Completely Randomized Design) and using SPSS software. The analysis was carried out on the level of sweetness, preference, and water content. The results showed that the water content at the maturity level of greenish yellow was 17.66%, the maturity level for shiny yellow was 17.33% and the maturity level was brownish yellow with black spots was 18%. The sweetness level of greenish yellow bananas is 13.66%, the maturity level is shiny yellow is 28.33%, the maturity level is brownish yellow with black spots is 29.66%. The higher the maturity level of the banana, the higher the level of sweetness of the banana. From the results of the preference level of sale bananas from the maturity level of greenish yellow, shiny yellow and brownish yellow with black spots, the preferred level of preference is the maturity level of shiny yellow.